A comparative study of metabolic profile, anthropometric parameters among vegetarians and non-vegetarians- do vegetarian diet have a cardio protective role? - ., Ashwini (International Journal of Research in Medical Sciences, 2017)
Background: Various studies have evaluated the cardio protective role of vegetarian diet among diverse group of population and found that vegetarians have lower cardiovascular risk. However, studies’ evaluating association between vegetarian diet and cardiovascular risk among young adults are meagre and is of special interest as they are the productive group of community. Methods: Ninety volunteers (age 19±1 year), of which 46 non-vegetarians, and 44 vegetarians were recruited. After obtaining written informed consent and Institutional Ethical Clearance, height, weight, waist circumference, hip circumference, fasting blood sugar, serum cholesterol, triglycerides and high density lipoproteins were estimated. Results: Significant difference was observed in weight, body mass index (BMI), waist circumference (WC), hip circumference (HC). Weight, BMI, WC, HC was lower among vegetarians compared to non-vegetarians and was statistically significant (p=0.0001, p=0.0001, p=001, p=0.0001 respectively). Serum cholesterol levels were also significantly lower among vegetarians. (p=0.01). HDL levels were 50.57±9.62 and 62.43±8.07 respectively for vegetarians and non-vegetarian group and was significantly higher among non-vegetarians (p=0.0001). Intergroup comparison among three group of vegetarians (lacto-ovo vegetarians, lacto vegetarians, total vegetarians) showed that total vegetarians have significantly lower height (p=0.001), weight (0.002), fasting blood glucose (p=0.001), total cholesterol (p=0.005) and triglycerides (p=0.0001) when compared to lacto-ovo vegetarians. Conclusions: Vegetarians have a more favourable lipid profile and anthropometry, with lower levels of total cholesterol, lower weight, body mass index, waist and hip circumference when compared to non-vegetarians, that reduces cardiovascular risk among them. Identifying young adults with unfavourable metabolic profile and adapting suitable dietary modifications tends to reduce the burden of cardiovascular disease particularly in developing countries.